Evidence of canonical somatic hypermutation in hairy cell leukemia - Arons, Evgeny (American Society of Hematology, 2011)
To compare hairy cell leukemia (HCL) with chronic lymphocytic leukemia (CLL) and normal B cells with respect to their B-cell receptors, somatic hypermutation (SHM) features in HCL were examined in a series of 130 immunoglobulin gene heavy chain rearrangements, including 102 from 100 classic (HCLc) and 28 from 26 variant (HCLv) patients. The frequency of unmutated rearrangements in HCLc was much lower than that in HCLv (17% vs 54%, P < .001) or historically in CLL (17% vs 46%, P < .001), but HCLv and CLL were similar (P = .45). As previously reported for CLL, evidence of canonical SHM was observed in HCLc rearrangements, including: (1) a higher ratio of replacement to silent mutations in the complementarity determining regions than in the framework regions (2.83 vs 1.41, P < .001), (2) higher transition to transversion ratio than would be expected if mutations were random (1.49 vs 0.5, P < .001), and (3) higher than expected concentration of mutations within RGYW hot spots (13.92% vs 3.33%, P < .001). HCLv met these 3 criteria of canonical SHM to a lesser extent. These data suggest that, whereas HCLc cells may recognize antigen-like CLL and normal B cells before malignant transformation, HCLv cells from some patients may originate differently, possibly without undergoing antigen recognition.